Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.31234/osf.io/bx9p7
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ta Det Onda Med Det Goda [Taking the Bad With the Good] - A Cultural Framework for Identity Narratives of Difficult Experiences in Sweden

Abstract: This study investigates the nature of narrating experiences of difficult life events among Swedish young adults. In doing so, we address a cultural framework for telling identity narratives of difficult experiences. Building on extant work on the importance of the narration of difficult life events for identity and wellbeing, we examine how these stories are narrated in the Swedish context, and relations between patterns of narration and well-being. Identity narratives about life challenges were collected from… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 7 publications
(16 reference statements)
0
7
0
Order By: Relevance
“…Further, neutral/vague sequencing is comparable to, though not coterminous with, our definition of "return". Eriksson et al (2020) found that redemptive sequences (in our scheme, similar to emergent) evinced greater scores on a growth coding scheme than neutral/vague sequences (in our scheme, similar to return).…”
Section: Narrated Growthmentioning
confidence: 48%
See 4 more Smart Citations
“…Further, neutral/vague sequencing is comparable to, though not coterminous with, our definition of "return". Eriksson et al (2020) found that redemptive sequences (in our scheme, similar to emergent) evinced greater scores on a growth coding scheme than neutral/vague sequences (in our scheme, similar to return).…”
Section: Narrated Growthmentioning
confidence: 48%
“…A recent study provides the most direct evidence for the association between narrated growth and redemptive forms. In a sample of Swedish young adults, Eriksson et al (2020) investigated four affective sequences (redemptive, neutral/vague, negative, and combination positive and negative) in narratives of difficult life events. In this study, redemptive sequences were defined as "narratives with a positive state of emotions to frame the difficult experience, such as ending with positive growth or increased understanding of the event", p. 163).…”
Section: Narrated Growthmentioning
confidence: 99%
See 3 more Smart Citations